Nutrition and Gastric Cancer - Carlo La Vecchia; Silvia Franceschi (Canadian Journal of Gastroenterology)
The reasons for the worldwide decline in stomach cancer incidence and mortality rates are not fully understood, but dietary changes are clearly implicated. While the possible mechanisms of gastric carcinogenesis and the impact of Helicobacter pylori eradication remain open to debate, at least two practical recommendations – to increase fruit and vegetable intake, and to reduce consumption of salt – are already supported by epidemiological evidence. These dietary recommendations may also be beneficial in the prevention of other cancers and chronic diseases. Promising evidence of a favourable effect of certain vitamins, such as vitamin C and E and betacarotene, and minerals, such as selenium, justifies additional investigation.